Multiparametric Prostate MRI in Biopsy-Naïve Men: A Prospective Evaluation of Performance and Biopsy Strategies - Krüger-Stokke, Brage; Bertilsson, Helena; Langørgen, Sverre; Sjøbakk, Torill Anita Eidhammer; Bathen, Tone Frost; Selnæs, Kirsten Margrete (Frontiers in Oncology, 2021)
Objectives: To prospectively estimate the diagnostic performance of multiparametric prostate MRI (mpMRI) and compare the detection rates of prostate cancer using cognitive targeted transrectal ultrasound (TRUS) guided biopsies, targeted MR-guided in-bore biopsies (MRGB) or both methods combined in biopsy-naïve men. Methods: Biopsy naïve men referred for mpMRI (including T2 weighted, diffusion weighted and dynamic contrast enhanced MRI) due to prostate cancer suspicion (elevated PSA or abnormal DRE) were eligible for inclusion. Images were scored according to PI-RADS v2, and men with PI-RADS 1 - 2 lesions were referred for routine systematic TRUS, while those with PI-RADS 3 - 5 lesions were randomized to MRGB or cognitive targeted TRUS. Men randomized to MRGB were referred to a secondary TRUS two weeks after MRGB. Gleason grade group ≥ 2 was defined as clinically significant prostate cancer. The performance of mpMRI was estimated using prostate cancer detected by any biopsy method as the reference test. Results: A total of 210 men were included. There was no suspicion of prostate cancer after mpMRI (PI-RADS 1-2) in 48% of the men. Among these, significant and insignificant prostate cancer was diagnosed in 5 and 11 men, respectively. Thirty-five men scored as PI-RADS 1-2 did not undergo biopsy and were therefore excluded from calculation of diagnostic accuracy. The overall sensitivity, specificity, negative predictive value and positive predictive value of mpMRI for detection of significant prostate cancer was 0.94, 0.63, 0.92 and 0.67, respectively. In patients with PI-RADS 3-5 lesions, detection rates for significant prostate cancer were not significantly different between cognitive targeted TRUS (68.4%), MRGB (57.7%) and combination of the two biopsy methods (64.4%). Median number of biopsy cores taken per patient undergoing systematic TRUS, cognitive targeted TRUS and MRGB were 14[8-16], 12[6-17] and 2[1-4] respectively. Conclusions: mpMRI in a cohort of biopsy-naïve men have high negative predictive value and our results support that it is safe to avoid biopsy after negative mpMRI. Furthermore, MRGB provides a similar diagnosis to the cognitive targeted TRUS but with fewer biopsies.